Impact of External Pressure, Tax Digitalisation, and CSR Disclosure on Financial Fraud - Tiara Sea Misa; Umiaty Hamzani; Khristina Yunita (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
This study investigates the influence of external pressure, tax digitalisation, and corporate social responsibility (CSR) disclosure on financial statement fraud in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020 to 2023 period. A quantitative approach was employed using purposive sampling, with secondary data from annual and sustainability reports. CSR disclosure was measured using the CSRI index based on GRI standards, while financial statement fraud was measured using the Beneish M-Score model. The findings indicate that external pressure significantly affects financial statement fraud, whereas tax digitalisation and CSR disclosure have significant adverse effects. These results highlight the importance of implementing digital taxation systems and CSR practices to mitigate the risk of financial statement fraud.